IELTS preparation and practice : reading and writing : Academic module - Sahanaya, Wendy; Lindeck, Jeremy; Stewart, Richard; Vũ Tài Hoa; Nguyễn Văn Phước; Ban biên dịch First News. (Đà Nẵng : Nxb Đà Nẵng, 2003)
Reading test; Writing test.
Keywords: English language; International English Language Testing Systems; IELTS; English language -- Textbooks for foreign speakers; English language -- Examinations, questions, etc